PENDIDIKAN GIZI INFORMAL KEPADA PENJAJA MAKANAN UNTUK PENINGKATAN KEAMANAN PANGAN JAJANAN ANAK SEKOLAH DASAR (INFORMAL NUTRITION EDUCATION TO FOOD VENDORS FOR IMPROVING SAFETY OF STREET-FOODS SELLING AT PRIMARY SCHOOL) - Evy Damayanthi; Khusnul Khotimah; Eddy Setyo Mudjajanto; Cesilia Meti Dwiriani; Lilik Kustiyah (Persagi, 2013)
ABSTRACT Street foods have an important role in contributing school children energy and nutriens need. Nationally, there is a serious problem on the safety of street food near schoool, therefore an effort is needed to overcome the problem. The objective of this study was to develop a simple model to solve the safety problem of street food near school. The study was conducted in two steps. The first step was done in 10 primary schools to determine the problem and to define the method of problem solving. One school with the worst food safety problem was selected as area of research. The second step was to implement the defined method into the selected primary school. Descriptive and inferensia analysis were applied in this study. Based on street food safety risk evaluation, the defined methods are nutrition extension and assistance to street food vendors in primary school SDN